Cor Triatriatum Dexter. Role of Echocardiography, Computed Tomography, and Magnetic Resonance Imaging in Its Diagnosis - N. V. Soroka; V. V. Abramyan; T. V. Stavenchuk; I. A. Shelestova; E. I. Zyablova; O. O. Khakhalina; N. G. Terentev (Инновационная медицина Кубани)
Cor triatriatum dexter is a rare congenital heart anomaly in which the right atrium is divided into 2 chambers by a membrane. Clinical manifestations vary depending on the degree of the right atrium separation and the presence of concomitant anomalies. We report a case of asymptomatic cor triatriatum dexter diagnosed during transthoracic echocardiography. The diagnosis was confirmed by transesophageal echocardiography, computed tomography, and magnetic resonance imaging. Transthoracic echocardiography is a sensitive primary diagnostic tool for such congenital heart disease as cor triatriatum dexter.